Mapping deformed hyperbolic potentials into nondeformed ones - Dutra, Alvaro de Souza [UNESP] (Elsevier, 2005)
In this work we introduce a mapping between the so-called deformed hyperbolic potentials, which are presenting a continuous interest in the last few years, and the corresponding nondeformed ones. As a consequence, we conclude that these deformed potentials do not pertain to a new class of exactly solvable potentials, but to the same one of the corresponding nondeformed ones. Notwithstanding, we can reinterpret this type of deformation as a kind of symmetry of the nondeformed potentials. © 2005 Elsevier B.V. All rights reserved.
Keywords: solvent; deformity; energy; mathematical analysis; mathematical computing; molecular interaction; parameter; physics